Determining strategies for the cadastre 2034 vision using an AHP-Based SWOT analysis: A case study for the turkish cadastral and land administration system - Polat, Zeynel Abidin; Alkan, Mehmet; Surmeneli, Hicret Gursoy (ELSEVIER SCI LTD, 2017)
This study aimed to identify the current land management and cadastre system in Turkey and determine the most appropriate strategy for integrating the current structure with the principles of the Cadastre 2034 vision. In this work, the legal, institutional, and technical (LIT) status of the existing land management and cadastre system in Turkey was determined using a method based on Strengths, Weaknesses, Opportunities, and Threats (SWOT) and Analytic Hierarchy Process (AHP). Initially, the advantages or weaknesses of the existing land management and cadastre system in Turkey in terms of LIT aspects, opportunities, and threats arising from the external environment were determined by the SWOT matrix. Then, the information obtained concerning the existing land management and cadastre system in Turkey using this matrix was integrated into AHP and the most appropriate strategy was determined in terms of LIT aspects. For the existing land management and cadastre system in Turkey, from the legal point of view, the best strategy with a weighting of 30% was to 'update the land administration legislation according to the conditions of the day'. The best strategy in terms of institutionalization was to 'disseminate in-vocational training for the training of qualified personnel (28% weighting)' and the best strategy from the technical perspective was identified as, 'the use of technical and technologically advanced measurement techniques in spatial data collection (38% weighting)'. The goal in implementing the AHP-Based SWOT method is to improve the quantitative information basis of strategic planning processes. So, SWOT provides the basic outline within which to perform an analysis of the decision situation, and the AHP assists in carrying out SWOT more analytically and in elaborating the analysis so that alternative strategic decisions can be prioritised.
Keywords: Cadastre 2034 vision; SWOT analysis; AHP; Cadastre; Land registry; GDLRC; Environmental Sciences & Ecology